Effective communication in conflict resolution process - Peredon, Nataliia; Передон, Наталія (Східноєвропейський національний університет імені Лесі Українки, 2014)
The article is dedicated to the linguistic analysis of the conflict resolution as the final stage of conflict interaction in English discourse. The author has made an attempt to describe speech behaviour of a communicator, who initiates resolving interpersonal conflict. Analysis of the examples taken from the British and American contemporary fiction make it possible to define the main verbal means that contribute to the implementation of intention to harmonize relations between the addresser and addressee. The usage of these means has been analyzed at lexical, syntactic and pragmatic level. The chief nonverbal and paraverbal means of communication which accompany the verbal embodiment of the aim to resolve a conflict have been identified. It has been found out that at the stage of conflict settlement the usage of the analyzed units is aimed at demonstration of the positive attitude to the partner in communication, showing genuine interest in resolving conflict, as well as the expression of the feeling of regret because of the contradictions that have emerged in relations with the addressee and the desire to restore the harmonious interaction. Стаття присвячена лінгвістичному аналізу розв’язання конфлікту як завершальної стадії конфліктної взаємодії в англомовному дискурсі. Зроблено спробу описати мовленнєву поведінку комуніканта, який ініціює вирішення міжособистісного конфлікту. На основі аналізу мовного матеріалу виділені домінантні вербальні засоби, що сприяють реалізації інтенції гармонізувати стосунки між адресантом та адресатом, проаналізовано їхнє вживання на лексичному, синтаксичному та прагматичному рівнях. Виділено основні невербальні та паравербальні засоби комунікації, що супроводжують вербальне втілення наміру оптимізації конфлікту. Встановлено, що на стадії розв’язання конфлікту застосування адресантом аналізованих засобів спілкування спрямоване на демонстрацію позитивного ставлення до партнера по комунікації, вияв власної зацікавленості у вирішенні конфлікту, а також вираження почуття жалю через суперечності, що виникли у стосунках з адресатом, і бажання відновити гармонійну міжособистісну інтеракцію.
Ефективна комунікація у процесі розв’язання конфлікту.
Keywords: conflict resolution; verbal; nonverbal; paraverbal means of communication; addresser; addressee; розв’язання конфлікту; вербальні; невербальні; паравербальні засоби комунікації; адресант; адресат